Constant regulation for stable CD8 T‐cell functional avidity and its possible implications for cancer immunotherapy. Issue 6 (30th March 2021) - Gilfillan, Connie B.; Hebeisen, Michael; Rufer, Nathalie; Speiser, Daniel E.
Abstract: The functional avidity (FA) of cytotoxic CD8 T cells impacts strongly on their functional capabilities and correlates with protection from infection and cancer. FA depends on TCR affinity, downstream signaling strength, and TCR affinity‐independent parameters of the immune synapse, such as costimulatory and inhibitory receptors. The functional impact of coreceptors on FA remains to be fully elucidated. Despite its importance, FA is infrequently assessed and incompletely understood. There is currently no consensus as to whether FA can be enhanced by optimized vaccine dose or boosting schedule. Recent findings suggest that FA is remarkably stable in vivo, possibly due to continued signaling modulation of critical receptors in the immune synapse. In this review, we provide an overview of the current knowledge and hypothesize that in vivo, codominant T cells constantly "equalize" their FA for similar function. We present a new model of constant FA regulation, and discuss practical implications for T‐cell‐based cancer immunotherapy. Abstract : The functional avidity (FA) of CD8 T cells is stably maintained, and similar despite different TCR affinities of the codominant clonotypes. We hypothesize that continued adjustment of the net coreceptor signal strength (i) compensates for the differences in TCR affinity and (ii) acts to keep FA stable despite changing T‐cell activation stages.